Breastfeeding Practice of Students and Workers Women in The University - Noviana Nur Sari; Citra Widya Kusuma; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat (BKM), 2020)
Praktik Perilaku Pemberian ASI Bagi Wanita Studiatau Bekerja Di UniversitasBreastfeeding Practice of Students and Workers Women in The UniversityNoviana Nur Sari1, Mubasysyir Hasanbasri2, Citra Widya Kusuma3          AbstractIntroduction: Breast milk plays a role in the growth and development of infants and prevent stunting. Mothers who work or study have support and obstacles in the breastfeeding process.Purpose: This research aims to explore practical experience resistance strategies to keep giving breastfeeding for working or studying mothers in the university.Method: This research is a qualitative case study design study. The subjects are working or studying mothers who have breastfeeding experience while working or studying for a maximum duration last two years including lecturers, employees, and students.Results: Working or studying mothers have various resistance strategies such as keep milk stock during three months leave, pumping before going to work and come home and pumping in the office. The various strategies are used by students moms to continue breastfeeding such as go home every breaking time of lectures to express milk, find the empty private spaces to express milk, and choose courses that have breaking time, pumping in the car when women go back to home. Working mothers feel a lot of support and there are no obstacles compared to student moms. They have strong self-efficacy due to the mother's determination to continue breastfeeding even though returning to work or study and the mothers want to give the best rights of the children successfully.Conclusion: Self-efficacy working or studying mothers is caused by a strong determination to succeed give breast milk and provide the best rights for their children. It is a motivating factor for mothers to carry out various resistance strategies successfully despite several obstacles.Keywords: breastfeeding, strategies, student mom, university, working women.